Mathematics Learning through Differentiated Student Worksheet based on Assemblr Edu - Arnidha, Yunni; Istiani, Ana; Wulandari, Yulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2025)
This study aims to develop differentiated student worksheet of learning media based on Assemblr Edu. Through the development of differentiated and innovative learning media, it can meet the diverse learning needs of students by considering the readiness, interests, and talents of students. The development model used is Dick and Carrey. The subjects of this study were fifth-grade students of SDN 1 Srirahayu, Pringsewu Regency, Lampung in the mathematics subject of cubes and cuboids. The results of the validation of material experts were 89.24% and media experts 91.21%, meaning that student worksheet based on Assemblr Edu is suitable for use as a trial. The trial went through the stages of small group trials, medium groups, and large groups. The results of the trial received a good response, with an average of 88%. The implications of the development carried out are an increase in understanding of the concept of cubes and cuboids, learning that is more interesting and innovative, more effective learning differentiation and the creation of learning independence.